Corrigendum: Self-Compassion and Aggression in College Students - Ferdi W. Djajadisastra (ANIMA Indonesian Psychological Journal, 2017)
After the publication of our article titled “Self-Compassion and Aggression in College Students” (Djajadisastra, 2017), we noted that some parts of the article need to be edited.